Stimulus-responsive liposomes for biomedical applications. Issue 8 (August 2021) - Antoniou, Antonia I.; Giofrè, Sabrina; Seneci, Pierfausto; Passarella, Daniele; Pellegrino, Sara
Graphical abstract: Highlights: Recent advances in internal stimuli-responsive liposomes have been reported. Chemical modifications on liposomes pave the way to smart stimuli triggered drug delivery systems. Pro-drug/liposome-combined systems enhance the therapeutic efficacy of their biological cargo. Abstract: Liposomes are amphipathic lipidic supramolecular aggregates that are able to encapsulate and carry molecules of both hydrophilic and hydrophobic nature. They have been widely used as in vivo drug delivery systems for some time because they offer features such as synthetic flexibility, biodegradability, biocompatibility, low immunogenicity, and negligible toxicity. In recent years, the chemical modification of liposomes has paved the way to the development of smart liposome-based drug delivery systems, which are characterized by even more tunable and disease-directed features. In this review, we highlight the different types of chemical modification introduced to date, with a particular focus on internal stimuli-responsive liposomes and prodrug activation.